2013
DOI: 10.1136/gutjnl-2013-304612
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione peroxidase 7 has potential tumour suppressor functions that are silenced by location-specific methylation in oesophageal adenocarcinoma

Abstract: Objective We investigated the potential tumor suppressor functions of glutathione peroxidase 7 (GPX7) and examined the interplay between epigenetic and genetic events in regulating its expression in oesophageal adenocarcinomas (OAC). Design In vitro and in vivo cell models were developed to investigate the biological and molecular functions of GPX7 in OAC. RESULTS Reconstitution of GPX7 in OAC cell lines, OE33 and FLO-1, led to significant growth suppression as demonstrated by growth curve, colony formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 41 publications
4
43
0
Order By: Relevance
“…We have recently reported that GPX7 protects esophageal epithelia from acidic bile salts-induced oxidative DNA damage and double strand breaks through modulating intracellular ROS 20. We also demonstrated that GPX7 has a tumor suppressor function that is silenced through location specific DNA hypermethylation in Barrett's carcinogenesis 23. In the present study, we show that GPX7 can suppress the bile salts-induced activation of NF-κB and up-regulation of pro-inflammatory, pro-tumor cytokines and chemokines, further supporting a tumor suppressor function of GPX7 in EAC.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…We have recently reported that GPX7 protects esophageal epithelia from acidic bile salts-induced oxidative DNA damage and double strand breaks through modulating intracellular ROS 20. We also demonstrated that GPX7 has a tumor suppressor function that is silenced through location specific DNA hypermethylation in Barrett's carcinogenesis 23. In the present study, we show that GPX7 can suppress the bile salts-induced activation of NF-κB and up-regulation of pro-inflammatory, pro-tumor cytokines and chemokines, further supporting a tumor suppressor function of GPX7 in EAC.…”
Section: Discussionmentioning
confidence: 82%
“…We have previously shown that GPX7 plays a tumor suppressor function in esophageal adenocarcinoma 23. Aberrant activation of NF-κB has been associated with inflammation and tumor development and progression 11, 30, 31.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutathione peroxidases (GPX) constitute a major antioxidative damage enzyme family [ 43 ] and are thus important in cancer therapy [ 44 ]. Not only genetic but also epigenetic mechanisms of gene regulation have been proposed for GPX7 , while recently a CpG island was identified as a key player in regulating GPX7 expression [ 45 ]. In total, we identified 87 SNPs in the GPX7 gene affecting the methylation of nine CpG sites (meQTL), with six of the sites being directly implicated in quantitative differences in the gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Other examples, which are connected to H 2 O 2 transit across the ER membrane, are granulocyte colonystimulating factor receptor signaling [29], oxidative DNA damage in response to cellular stresses [30][31][32], activation of survival pathways upon H 2 O 2 generation in the ER [33,34], and the regulatory roles of ER-luminal peroxidases in various settings of cytosolic signal transduction [29,[35][36][37][38]. These findings clearly indicate the permeability of the ER membrane for H 2 O 2 .…”
Section: H 2 O 2 Can Readily Permeate Through the Endoplasmic Reticulmentioning
confidence: 98%